Investigating the Effect of Correlation between Firms' Earnings and Announcement Timing on the Accruals - Hamid Haghighat; Mohammad Rahimpoor; Nikoo Khansari; Ramin Ghorbani (مطالعات تجربی حسابداری مالی, 2017)
Investigating the Effect of Correlation between Firms'''''''''''''''' Earnings and Announcement Timing on the Accruals